A biosensor based on a 3D-DNA walking machine network and distance-controlled electrochemiluminescence energy transfer for ultrasensitive detection of tenascin C and lead ions. Issue 63 (20th July 2018) - Xu, Zi-Qi; Zhang, Pu; Chai, Ya-Qin; Wang, Hai-Jun; Yuan, Ruo
Abstract : An electrochemiluminescence biosensor was proposed based on distance-controlled energy transfer and a 3D-DNA walking machine network. Abstract : An electrochemiluminescence biosensor was proposed based on distance-controlled energy transfer and a 3D-DNA walking machine network to significantly improve mass transport and offer an ultrasensitive and controllable strategy for the detection of different types of target.